Phenolic content and antioxidant activity of Pereskia grandifolia Haw. (Cactaceae) extracts - Sim, K.S.; Nurestri, A.M.S.; Norhanom, A.W. (Medknow Publications, 2010)
The leaves of Pereskia grandifolia Haw. (Cactaceae), commonly known as "Jarum Tujuh Bilah" in Malaysia, have been traditionally used as natural remedy in folk medicine by the locals. In the present study, the antioxidant potential of P. grandifolia crude methanol and its fractionated extracts (hexane, ethyl acetate and water) have been investigated, employing three different established testing systems, such as scavenging activity on 1,1-diphenyl-2-picrylhydrazyl (DPPH) radicals, reducing power assay and β-carotene method. The total phenolic content of the P. grandifolia extracts was also assessed by the Folin-Ciocalteau's method. The ethyl acetate extract showed significantly the highest total phenolic content, DPPH scavenging ability and antioxidant activity in β-carotene bleaching assay while the hexane extract possessed significantly strongest reducing power. The data obtained in these testing systems clearly establish the antioxidant potency of P. grandifolia. As such, this is the first report on the antioxidant activities of P. grandifolia.